Instilling PAK Values using Augmented Reality as an Innovative Learning Media - Ratu Mofu, Benyamin Dadi; Kolibu, Dirk Roy (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to explore the use of Augmented Reality (AR) technology in Christian Religious Education at Jayapura Joint High School. At Jayapura Joint High School, although there have been various learning methods applied, the use of Augmented Reality (AR) as a learning medium in Christian Religious Education (PAK) has not been used. This shows the untapped potential to improve the student learning experience. This research is a qualitative research. This approach was chosen because it aims to understand the phenomenon that occurs in the context of Christian religious education at Jayapura Joint High School through the use of Augmented Reality (AR) technology. The case study approach, allows researchers to investigate complex phenomena in real contexts. One of the key findings of this study is the improvement of material understanding among students who use AR as a learning medium. Students who learn to use AR show a much higher level of engagement in the learning process compared to traditional learning methods. One of the main challenges is the need for adequate hardware. Research reveals that the use of (AR) in education, especially in instilling PAK (Christian Religious Education) values, shows significant results in increasing student understanding and engagement. The results show that students who learn through AR have a higher level of information retention compared to traditional methods. AR can increase student engagement in PAK learning which has a positive impact on their learning motivation.